PENERAPAN TERAPI BERMAIN BONEKA TANGAN PADA AN. K USIA PRA SEKOLAH (3-6 TAHUN) UNTUK MENGURANGI KECEMASAN PADA PENYAKIT TYPOID DI RUMAH SAKIT DUSTIRA TANGGAL 12-13 MEI 2023 - Pangestu Dewi, Pugar; Zulva, Siti (Yayasan Putra Sukamanah Sejahtera, 2024)
Typoid fever is a disease that attacks the digestive system by Salmonella typhi bacteria, this disease can affect anyone, including children. The City of Cimahi has an incidence of Typhoid of 70 cases per 2022. At the Dustira Cimahi Hospital the number of Typoid cases in preschool children is 62 cases. This makes children need hospital care, and causes anxiety in children due to hospitalization. Feelings of anxiety are the impact of treatment experienced by children. To reduce this anxiety, play therapy can be given to children. There are several types of games for these children, such as puzzles, snakes and ladders, coloring and one of them is hand puppets. Hand puppets are simple games that can be done anywhere. To reduce this anxiety, play therapy with hand puppets can be given. This application aims to determine the effect of playing hand puppet therapy on reducing the anxiety level of children who are undergoing treatment at Dustira Cimahi Hospital. This study uses a qualitative descriptive method, namely the case study approach to nursing care and describes the problem by conducting assessments to collect data, formulate nursing diagnoses, carry out nursing planning, and carry out implementation and can evaluate the results of nursing care. It was found that children experienced anxiety on a scale of 4 (moderate anxiety) with facial expressions wrinkled downwards, fussy, said they were afraid of being injected. The implementation carried out was playing hand puppet therapy, the evaluation obtained was in the form of an anxiety assessment with the Facial Image Scale before being given therapy and after therapy.